The Informatics of Time and Events - Gérard Berry (Collège de France, 2015)
The management of time and events is central to various domains of informatics, from embedded circuits and software programs in all sorts of objects to musical creation, or the simulation of physical phenomena. Yet this subject receives little attention in classical informatics. This lecture presents different types of time and event modelling associated with new programming languages. It discusses the notions of density of the moment and of hierarchical and multiform times created by the rep...